New nanodrug design for cancer therapy: Its synthesis, formulation, in vitro and in silico evaluations - Budama-Kilinc, Yasemin; Kecel-Gunduz, Serda; Ozdemir, Burak; Bicak, Bilge; Akman, Gizem; Arvas, Busra; Aydogan, Feray; Yolacan, Cigdem (WILEY-V C H VERLAG GMBH, 2020)
The aim of this study was to develop a novel nanosize drug candidate for cancer therapy. For this purpose, (S)-methyl 2-[(7-hydroxy-2-oxo-4-phenyl-2H-chromen-8-yl)methyleneamino]-3-(1H-indol-3-yl)propanoate (ND3) was synthesized by the condensation reaction of 8-formyl-7-hydroxy-4-phenylcoumarin withl-tryptophan methyl ester. Its controlled release formulation was prepared and characterized by different spectroscopic and imaging methods. The cytotoxic effects of ND3 and its controlled release formulation were evaluated against MCF-7 and A549 cancer cell lines, and it was found that both of them have a toxic effect on cancer cells. For drug design and process development, the molecular docking analysis technique helps to clarify the effects of some DNA-targeted anticancer drugs to determine the interaction mechanisms of these drugs on DNA in a shorter time and at a lower cost. By using the molecular docking analysis and DNA binding assays, the interaction between the synthesized compound and DNA was elucidated and non-binding interactions were also determined. To predict the pharmacokinetics, and thereby accelerate drug discovery, the absorption, distribution, metabolism, excretion and toxicity values of the synthesized compound were determined by in silico methods.
Keywords: anticancer; coumarin derivative; DNA binding; molecular docking; nanoparticle; ANTICANCER ACTIVITY; COUMARIN DERIVATIVES; DNA-BINDING; BIOLOGICAL EVALUATION; NANOPARTICLES; Pharmacology & Pharmacy; Chemistry